Continuous improvement technique and its role in costs reduction - Forat Sattar Hassoon, Ali Abdul-Hussein Hani Al-Zameli, Hayder Oudah Kadhim, (Opción, 2019)
The research aims to study continuous improvement technique and its role in reducing unnecessary and unjustified costs. In addition to this, this study investigated the ways to improve the value of products for customers as well as for company. Furthermore, customer requirements with the product and business have given adequate importance accompanying changes in production techniques for cost management. The research has addressed the knowledge-based technique of continuous improvement in terms of its concept, importance, tools, elements and steps to be applied in production units.